Galileo and the universe - Parker, Steve (New York : Harper Collins, 1992)
Discusses the life and discoveries of Galileo, the sixteenth- and seventeenth-century mathematician, physicist, and astronomer who challenged ideas more than a thousand years old and changed the course of science
Includes glossary and index
Primary
Keywords: Galilei, Galileo -- 1564-1642 -- Biography -- Juvenile literature; Astronomy -- History -- Juvenile literature; Astronomer -- Italy -- Biography -- Juvenile literature